2011
DOI: 10.1038/onc.2011.23
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidences for the chemosensitizing efficacy of liposomal curcumin in paclitaxel chemotherapy in mouse models of cervical cancer

Abstract: The microtubule-targeting antineoplastic agent, paclitaxel, is highly efficacious against a wide spectrum of human cancers. However, dose-limiting toxicity and development of drug resistance limit its clinical application. Development of novel strategies that overcome chemoresistance and sensitize cancer cells to paclitaxel can enhance the therapeutic effect of this drug. We have previously shown that curcumin, a natural polyphenol, enhances paclitaxelinduced cytotoxicity in vitro through downregulation of nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
138
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(150 citation statements)
references
References 64 publications
10
138
0
2
Order By: Relevance
“…Inhibition of PGE 2 -miR-21 signaling restored PTEN levels to baseline and decreased AKT activation , which was mirrored by a drop in cell viability due to the augmented induction of apoptosis . These findings have been validated by other reports that causally related curcumin-induced apoptosis in Cancer Pharmacology of Curcumin cancer cells to suppressed PGE 2 synthesis Lee et al, 2009;Sreekanth et al, 2011) and/or decreased AKT phosphorylation Elamin et al, 2010;Watson et al, 2010a;Prakobwong et al, 2011;Wong et al, 2011). c. Angiogenesis (H-VII). The angiogenic switch (Bergers and Benjamin, 2003) is primarily triggered by VEGF (Keck et al, 1989;Leung et al, 1989), the expression of which is upregulated in most human cancers (Ferrara and Davis-Smyth, 1997).…”
Section: +supporting
confidence: 80%
“…Inhibition of PGE 2 -miR-21 signaling restored PTEN levels to baseline and decreased AKT activation , which was mirrored by a drop in cell viability due to the augmented induction of apoptosis . These findings have been validated by other reports that causally related curcumin-induced apoptosis in Cancer Pharmacology of Curcumin cancer cells to suppressed PGE 2 synthesis Lee et al, 2009;Sreekanth et al, 2011) and/or decreased AKT phosphorylation Elamin et al, 2010;Watson et al, 2010a;Prakobwong et al, 2011;Wong et al, 2011). c. Angiogenesis (H-VII). The angiogenic switch (Bergers and Benjamin, 2003) is primarily triggered by VEGF (Keck et al, 1989;Leung et al, 1989), the expression of which is upregulated in most human cancers (Ferrara and Davis-Smyth, 1997).…”
Section: +supporting
confidence: 80%
“…Curcumin inhibits proliferation and induces apoptosis in cancer cells via suppression of the AKT pathway , Sun et al 2010, Duarte et al 2010, Saini et al 2011, Prakobwong et al 2011, Zanotto-Filho et al 2011, Sreekanth et al 2011. Moreover, it decreases cell growth via inactivation of NF-κB, preventing DNA binding, nuclear translocation, and p65 phosphorylation.…”
Section: Potential Chemo Preventative Agentsmentioning
confidence: 99%
“…This result may be associated with the inhibition of proliferation and the induction of apoptosis and cell cycle arrest in endothelial cells in vitro. Liposomal curcumin has been reported to exhibit anti-cancer activity on colorectal cancer (19), prostate cancer (20), head and neck squamous cell carcinoma (21), and pancreatic (22) and cervical cancer (23). In this study, we revealed that liposomal curcumin inhibits tumor growth in the Lewis lung cancer mouse model primarily by targeting tumor angiogenesis.…”
mentioning
confidence: 71%